2013
DOI: 10.1111/jocn.12338
|View full text |Cite
|
Sign up to set email alerts
|

Women's experiences of infertility – towards a relational model of care

Abstract: Psychosocial skills are recognised as core competences for fertility nurses. A relational conceptualisation of patient's experiences, living with and through infertility, provides further information for the development of staff and enhanced knowledge and practice skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 32 publications
1
39
0
4
Order By: Relevance
“…Studies were conducted in the UK ( n = 5), USA ( n = 4), Africa ( n = 4), Iran ( n = 3), Australia ( n = 2), Pakistan ( n = 2), Portugal ( n = 1), Israel ( n = 1), China ( n = 1), Italy ( n = 1), India ( n = 1) and Taiwan ( n = 1). A multinational approach was addressed in two online studies (Cunningham & Cunningham, ; Toscano & Montgomery, ). Two articles simultaneously presented English and Pakistani participants (Batool & Visser, ) and English and Iranian individuals (Roudsari & Allan, ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies were conducted in the UK ( n = 5), USA ( n = 4), Africa ( n = 4), Iran ( n = 3), Australia ( n = 2), Pakistan ( n = 2), Portugal ( n = 1), Israel ( n = 1), China ( n = 1), Italy ( n = 1), India ( n = 1) and Taiwan ( n = 1). A multinational approach was addressed in two online studies (Cunningham & Cunningham, ; Toscano & Montgomery, ). Two articles simultaneously presented English and Pakistani participants (Batool & Visser, ) and English and Iranian individuals (Roudsari & Allan, ).…”
Section: Resultsmentioning
confidence: 99%
“…).Nonetheless and regardless of who performs the procedure, patient‐centred care could increase users’ satisfaction (Dancet et al . , Cunningham & Cunningham ) and this should be considered the cornerstone when designing and providing services to people involved in the infertility process.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that nurses and midwives should do research on infertile people who undergo infertility treatment and assisted reproduction techniques in their practice (Wilson & Leese ). Understanding these women's experiences may help nurses and physicians to offer better patient‐centred care (Cunningham & Cunningham ).…”
Section: Introductionmentioning
confidence: 99%
“…While there are many coping strategies that might be employed to try to come to terms with the experience of infertility (Callan & Hennessey, 2011), these strategies must be further developed, adapted and applied within, through and beyond the clinic. A model of care is required that recognises experience in transition (Cunningham & Cunningham, 2013) and regardless of treatment out-come. The fertility nurse may have an important role to play within this supportive framework.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, many women negotiate the normative expectations surrounding fertility and reproductive success, often beginning in childhood and emphasising the social condition of infertility (Cunningham & Cunningham, 2013). As the following section illustrates, earlier life course assumptions and anticipations are both condensed and heightened during this period, affecting the ability to adapt and transition through and beyond treatment.…”
Section: ' Hopefulness 'mentioning
confidence: 97%